Detection of Philadelphia chromosome by GTG-banding technique and bcr-abl fusion gene by reverse-transcription polymerase chain reaction for chronic myelogenous leukemia: A study of 29 patients - Amarillo, Ferdinand Enginco (Animo Repository, 2001)
Chronic myelogenous leukemia (CML) is a unique myeloproliferative disorder usually associated with a distinctive cytogenetic abnormality, the Philadelphia (Ph) chromosome and the bcr-abl fusion gene that leads to leukemogenesis. Cytogenetic analysis using GTG-banding (G-bands by Trypsin using Giemsa) technique and reverse-transcription polymerase chain reaction (RT-PCR) were used to determine the detection rate of the Philadelphia (Ph) chromosome and bcr-abl mRNA transcript, respectively, from peripheral blood of 23 and bone marrow of 6 Filipino patients with CML. Of the 29 CML patients studied, 4 were virgin cases, 22 were following a hydroxyurea and allopurinol therapy, and 3 were receiving interferon-alpha combined with hydroxyurea. Only 17 patients (59 percent) had adequate metaphase spreads of cytogenetic studies. The analysis revealed the presence of the Philadelphia (Ph) chromosome in all of the 17 patients (100 percent). In the first round of amplification, only 1 patient (3.4 percent) showed a bcr-abl product. However, in the nested RT-PCR, the method amplified the bcr-abl transcript in 28 patients (96.6 percent). The b3a2 fusion gene was detected in 15 patients, while the b2a2 fusion gene in 7 patients (24.1 percent), and both PCR products were detected in 7 patients (24.1 percent). Only patient 15 did not reveal any PCR product during the first and second rounds of amplification. RT-PCR results on bcr-abl detection were compared with those Philadelphia-positive cells obtained using GTG-banding. Comparatively, RT-PCR technique has a much higher detection rate (96.6 percent) than cytogenetic analysis (59.0 percent). Only 9 patients had decreased white blood cell count and platelet count after chemotherapy. All patients that had cytogenetic analysis and RT-PCR results showed nocytogenetic and molecular remission after receiving hydroxyurea and interferon-alpha or allopurinol.